2019
DOI: 10.1177/2516602619826261
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Health of the Santals: A Study of Selected Villages of Birbhum

Abstract: The study discusses the influence of social, economic and cultural factors on healthseeking behaviours of the Santals living in six villages of Birbhum district in West Bengal, India. By employing both qualitative and quantitative methods, data were collected for the study. The analysis shows the link between educational, social, economic and cultural factors and health-seeking behaviour. Lack of economic freedom was found as the predominant indicator in restricting access to better health-care facilities. Poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Poor hygiene of the surroundings was seen in all the study participants. Similar findings were seen in a study conducted by Asok kumar Sarkar, 11 where none of the villages have proper drainage and sewage management systems in place. Illiteracy and Ignorance could be the main reasons for poor hygiene in the surroundings.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Poor hygiene of the surroundings was seen in all the study participants. Similar findings were seen in a study conducted by Asok kumar Sarkar, 11 where none of the villages have proper drainage and sewage management systems in place. Illiteracy and Ignorance could be the main reasons for poor hygiene in the surroundings.…”
Section: Discussionsupporting
confidence: 86%
“…Among the study population, alcoholism was the major (50%) addiction followed by smoking(7.1%). Different findings were seen in a study conducted by Asok kumar Sarkar, 11 where Smoking is widely prevalent than chewing tobacco and drinkingalcohol.…”
Section: Discussionmentioning
confidence: 62%
“…The information regarding the sociodemographic factors recorded showed that among the Santhal tribe majority (40.7%) were educated till the level of primary or below, this low literacy among tribes is considered to be a primary cause of their socioeconomic backwardness which is depicted in the study findings and is in accordance to other studies. [ 11 12 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…12 Economic support extended by institutions and affordability of the individuals are predominant indicators that influence their health seeking behaviour. 7,13,14 The high cost and unavailability of modern health care system has serious implication for the livelihood of the poor households. 15 The role of education in the context of health access is significant.…”
Section: Introductionmentioning
confidence: 99%
“…Studies identified that education level of the individual is positively linked to health awareness and better health access. 14,16,17 A common believe that people carry regarding the cause of illness is owing to the evil touch, evil eye, blind faith, black magic, spirit call, stormy wind and village deity etc. In Sweden, the believes of the Christianity influence the hospital chaplaincy.…”
Section: Introductionmentioning
confidence: 99%